Professional Self-Realiazation as Mentalhealth Factor of Public Service Personell - Malimon, Liudmyla (Psychological Prospects Journal, 2018)
The article is devoted to the professional self-realization consideration as important factor of mental health preservation of publicl service personnel. The decrease of professional self-realization prestige in this sphere due to the fall of public confidence in government institutions, as well as high requirements to the professionalism level and personality qualities of specialists: honesty, morality, responsibility, emotional balance and readiness to serve the state and its citizens have been indicated. The psychological peculiarities of professional activity in the public service system have been described, in particular its increased stressogenic factors, that require constant reserves of self-control and self-regulation of public service employees. Characteristics of professional self-realization and personality mental health have been defined. The peculiarities of interrelation of qualitative characteristics of professional self-realization, personality self-actualization and subjective well-being of respondents have been outlined, based on what the general criterial features of mental health of an employee in the system of public service have been described. It has been determined, that professional self-realization is significant for the respondents, and manifests itself in order to achieve the peaks of professional development, to become professional in own business, to get high social status, to achieve the defined goals and objectives, to gain recognition of own merits, to deal in one’s own favorite business. It has been noted, that system of measures for the mental health protection of an employeee at workplace should include the complex of direct psychological interventions (assistance in personality problems overcoming, personal growth and self-improvement activization, etc.), as well as psychological support of organizational changes to form conditions for professional self-actualization of employees in order to prevent and preserve their mental health.